Epidemiologic Characteristics of Patients Admitted to Emergency Department with Dermatological Complaints; a Retrospective Cross sectional Study - Kilic, Deniz; yigit, ozlem; Kilic, Taylan; Buyurgan, Cagri Sefa; Dicle, Ozlem (Archives of Academic Emergency Medicine, 2019)
Introduction: Dermatological diseases constitute 5-8% of all emergency department (ED) visits. However, little is known about these patients. The aim of this study is to determine the epidemiologic characteristics of patients admitted to ED with dermatological complaints. Methods: This is a retrospective cross-sectional study conducted in the ED of a university hospital. Patients over 18 years of age who presented to ED with the following complaints were included in the study: rash, pruritus, and edema sensation in the throat or shortness of breath due to an allergic reaction. Demographics, chief complaints, final diagnoses, triage categories, consultations and hospitalization rates were obtained through computerized database of the hospital.Â Results: 859 patients were included in the final analysis. 511 (59.5%) patients were female and the mean age of patients was 39.03Â±15 years. The most common complaint and final diagnosis were skin rash with pruritus (50.9%) and urticaria with drug eruptions (84.5%), respectively. Two patients (0.2%) had an emergent triage category. 804 (93.6%) patients were discharged from ED, while 55 (6.4%) received consultations, resulting in 19 (34.5%) hospitalizations. Conclusion: Most of the patients admitted to ED with dermatological complaints are non-urgent and can be treated as outpatients. However, physicians should be alert for emergent causes, as well.